Comparing Conventional and Modern Methods for The Phycocyanin Extraction from Spirullina sp - Dian Marlina; Desi Purwaningsih; Reny Pratiwi; Ryan Werytama Saputra; Widiastuti Setyaningsih; Supriyono Supriyono (Advance Sustainable Science Engineering and Technology, 2024)
Spirulina platensis, a blue-green algae abundant in tropical regions, is rich in minerals, vitamins, fibers, and pigments, with low nucleic acid content. It has unique chromoproteins called phycobiliproteins, notably phycocyanin, used in various applications. This study aims to optimize phycocyanin extraction using different solvents (distilled water and sodium phosphate buffer pH 6.7) and methods (freeze-thaw and sonication). Spirulina platensis biomass was extracted in both solvents, then some of them was freeze for 24 and 48 hours followed by thawing overnight. The other was sonicated for 2.5 minutes, 50 Hz then soaked for 1, 2, and 3 hours. All of the samples were centrifuged at 6000 rpm for 10 minutes and the absorbance was measured using a UV-Vis spectrophotometer at wavelengths of 280, 620, and 650 nm. with freeze-thawing for 48 hours yielded the highest phycocyanin concentration (0.55%), with a yield of 11.07 and purity of 0.21. Sonication improved phycocyanin concentration, yield, and purity significantly, yielding 1.108, 25.85, and 0.26, respectively.